CESifo World Economic Survey May 2014 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Elisabeth Wieland (CESifo World Economic Survey, 2014)
World Economic Climate: World economic climate weakens, but remains at a high level - Economic Expectations: Optimistic economic expectations - Inflation: Moderate inflation expectations - Currencies: US dollar expected to rise - Interest Rates: Stable interest rates expected - Special Topic: Effects of large- scale government bond purchases by central banks
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies